Islam in contemporary Africa on violence, terrorism and development - Oladosu, Afis Ayinde (Cambridge Scholars Publishing, 2007)
Islam in Contemporary Africa: On Violence, Terrorism and Development features essays which are written by scholars, Christians and Muslims, on their experience of Islam and the Muslims in the continent of Africa and how tterrorism and violence have impacted intra-African harmony and cross-cultural understanding in the world today.